Exploring the Manifestation of Critical Thinking in the Moroccan Textbooks of English: The Case of "Ticket 2 English": Menjelajahi Manifestasi Berpikir Kritis dalam Buku Ajar Bahasa Inggris Maroko: Kasus "Ticket 2 Bahasa Inggris" - Jebbour, Mohsine (JEES (Journal of English Educators Society), 2019)
The purpose of this study was to explore whether Ticket 2 English, a Moroccan textbook of English, includes elements of critical thinking, which refers to the skill and disposition to select, collect, analyze, and evaluate information effectively. Descriptive analysis was employed to document instructions and activities that support the inclusion of critical thinking (CT) elements in the textbook. Results suggest that Ticket 2 English includes most of the skills found in Bloom’s taxonomy, important critical thinking dispositions, and some activities for teaching critical thinking. Yet, textbook designers need to supplement textbooks of English with additional activities, and high school teachers of English need to implement new teaching materials and practices to help enhance students’ level of critical thinking.